Застосування елементів діджіталізації в навчальному процесі ЗВО мистецького спрямування - Гуменюк Володимир; Humenyuk Volodymyr; Полубоярина Ірина; Poluboyaryna Iryna (Видавництво «Код», 2025)
Резюме. У статті наголошується на зростаючій ролі впровадження у професійну підготовку здобувачів вищої музичної освіти цифрових технологій. Визначено, що розробники концептуальних положень Четвертої промислової революції стверджували, що глобальна конкуренція національних систем вищої освіти заснована на застосуванні інноваційних форм цифрових технологій; можливостей штучного інтелекту для підвищення ефективності та продуктивності навчального процесу. Українські науковці пов’язують це явище з такими освітніми тенденціями, як глобалізація та швидкий технічний прогрес в усіх галузях науки та різних сферах діяльності суспільства.

Abstract. The article emphasizes the growing role of introducing digital technologies into the professional training of applicants for higher musical education. The developers of the conceptual provisions of the Fourth Industrial Revolution argue that the global competition of national higher education systems is based on the application of innovative forms of digital technologies; the capabilities of artificial intelligence to increase the efficiency and productivity of the educational process. Ukrainian scientists associate this phenomenon with such educational trends as globalization and rapid technical progress in all branches of science and various spheres of society. It is found that the digitalization of education is a complete transformation of the educational sphere through the introduction of modern digital technologies to achieve innovative development. This process includes the transfer of all processes, data and interaction of subjects into electronic format, the use of artificial intelligence, cloud services, the Internet and other tools to increase efficiency, optimize processes and create new opportunities. Such concepts as «digital competence» and «digital cultur» are defined. This made it possible to further develop the structure of these concepts. Digital competence of scientific and pedagogical workers and students of higher musical education can be defined as the readiness to master and use innovative methods, forms and means of teaching in musical and professional activities using technological tools of digitalization and the ability of subjects of the educational process to integrate them with their own professional experience to intensify learning and teaching, effective interaction that meets the challenges of today. Digital competence includes the presence of technical skills, media competence, information awareness, the ability to create digital content and ensure digital security
Application of digitalization elements in the educational process of the arts direction department
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: суб’єкти освітнього процесу; цифрові технології; діджіталізація музичної освіти; цифрова компетентність; цифрова культура